“La Alimentación y los problemas en el aprendizaje” - Quinchuela Rojas, Sylvia Patricia (2024)
The research aimed to provide a critical analysis of the challenges posed by nutritional deficits for students. It sought to determine how such deficits affect the learning outcomes of boys and girls studying at the ‘Loja’ Basic Education School. The findings of this study suggest that nutritional deficits are a significant factor contributing to the emergence of learning problems in the classroom, so a methodology based on the socio-critical paradigm, mixed approach, type of descriptive research, and inductive research method was employed in this study. Research techniques such as observation, interview, and surveys were used, along with their respective instruments: observation guide, interview guide, and questionnaire. The results of this study have significant implications for the social, educational, and family domains. The study concludes that sufficient evidence supports the presence of nutritional deficits among the students, which substantially predisposes the appearance of learning problems.